EXPLORING THE EFFECTS OF TEACHING TECHNIQUES ON THE ENJOYMENT OF MUSIC - Rossi , Elena (Ayden International Journal of Education and Social sciences, 2024)
Music education aims to nurture individuals' understanding and respect for music, with an emphasis on the ability to enjoy and appreciate music deeply. Developing the skill of perceiving the nuances of lyrics and instruments enhances the listener's experience and allows them to connect with the emotions conveyed by composers. In higher education, music appreciation courses play a pivotal role in fostering music comprehension and aesthetic orientation. These courses are increasingly offered as public courses in universities, aiming to acquaint students with the fundamentals of music while cultivating their appreciation for the diverse facets of this art form. To achieve a higher level of music appreciation among students, universities must explore innovative approaches that not only motivate students to learn music for pleasure but also encourage a profound connection with the art itself. This paper delves into the significance of music appreciation in higher education and the need for strategies to enhance students' understanding and engagement with music.